Development of a web-based materials testing system - Bal, Mert; Hashemipour, Majid; Bayindir, Suha (Inderscience Enterprises Ltd, 2005)
A web-based materials testing system has been developed which can easily be adapted to varying demands of laboratory instruction. It consists of several test machines upgraded by implementing a data acquisition system with a module-based control software called MULTIMOS (Multi-Testing Machines Operating Software). MULTIMOS is a flexible and user-friendly software that has been developed for performing measurements and automating laboratory instruments. It provides a number of modules to control various materials science experiments in the laboratory. MULTIMOS also provides configuration and modification modules to allow the system users to modify the current system or to add new laboratory instruments to the system for automation. The overall system upgrades the laboratory into an online test centre, which can be accessed to perform remote laboratory experiments and simultaneously receive the test results from the test machines located in the materials science laboratory.
Keywords: data acquisition; laboratory equipment and automation; operating software; remote experimenting; upgrading